[Retraction] The Effect of Picture Series to the Students’ Ability in Writing Narrative Text - Mentari Florentina Pasaribu; Riana Br Sianipar; Marintan Simbolon; Vivi Anzelina (Scripta : English Department Journal, 2020)
This research is intended to know the effect of using picture to the students’ ability in writingnarrative text. In order to answer the problem, the researchers use some theories, namely: Cohen andRiel (1989), Byrne (1997), Heaton (1988), Callahan (1992). In this article, the researchers usequantitative methodology. Researchers use students at SMAS Dharma Pancasila Medan grade XI as thepopulation and use 58 students as the sample. The instrument in this article is a written test and the testis about writing Narrative text. From the data analysis, the researchers give the score of each student inevery group and calculate it, the researchers find that the result of analyzing the data, the score of t-testis higher than t-table, where the t-table is 2.00 and t-test is 7.00. So, t-test is higher than t-table. Thedata analysis shows that there is a significant effect in using series of picture to the ability of the studentsin writing narrative text at grade XI of SMAS Dharma Pancasila. It meant that Ha was accepted H0 wasrejected.